PENGARUH PERKEMBANGAN LAHAN TERBANGUN TERHADAP KUALITAS LINGKUNGAN PERMUKIMAN (Studi Kasus: Kawasan Pendidikan Kelurahan Tembalang) - Yuliastuti, Nany; Fatchurochman, Arif (Universitas Diponegoro, 2012)
The existence of educational activities in the Tembalang sub-district consequence the emergence of other activities to support educational activities, among other activities of living, trade and services and so on. The diversity of activity and increasing numbers of migrants implies built up area increasing for housing and supporting facilities and infrastructure. The purpose of this study is to explain the influence of built up area development to the quality of the settlement environment in the Tembalang educational area. This study uses quantitative methods by using analytical techniques, including identification, correlative analysis, and descriptive analysis. Built up area developments in settlement area of Tembalang from 2006 - 2010 increased for 48% (27 395 m2) from the conditions at the beginning of the year 2006 with an average increase for 6848.77 m2 or about 12% of the area in 2006. The quality of settlement environment viewed from the physical aspects including building density conditions, the basic coefficient buildings, settlement infrastructure and settlement facilities show conditions are quite good quality. The condition of built up area development give a positive influence on scores from the quality of settlement environment by the equation Y = 0,256 x – 0,30. This means required at least 2% of built up area development which increase the quality of settlement infrastructure to improve the quality of settlement environments.